Exploring the Effect of Mobbing in Vocational Secondary Schools on Teacher Performance - Zeynep Çetin; Miray Özözen Danacı (Connectist Istanbul University Journal of Communication Sciences)
Recent psychological and physical harm to teachers preventing educational institutions from achieving their objectives has motivated our investigation into the effect of mobbing in vocational secondary schools on the performance of teachers. It has been predicted that the person subject to mobbing may work more efficiently due to higher ambition or fear culture or on the contrary may have a lower performance. Thus, the present study was designed to determine the relationship between mobbing in educational institutions and performance. The study sample consists of 251 teachers; 130 females and 121 males, employed in the vocational secondary schools of the Ministry of National Education in the province of Düzce. The data collection tools used in this study were chosen by taking into account the variables to be measured and included the Personal Information Form which consisted of gender, vocation seniority, branch, educational level, and age information of teachers in secondary schools, the Mobbing Scale consisting of 23 items and developed by Özözen-Danacı (2009), and the Teacher Performance Enhancement Survey, a 5-point Likert scale consisting of 26 items. Results of the study indicated a significant negative relationship between mobbing and performance; female teachers were more exposed to mobbing than male teachers; and, junior teachers suffered the most from mobbing. Awareness of the mobbing phenomenon and necessary preventive measures in education institutions, the informing of teachers and educators and the general consciousness between school personnel about mobbing should be ensured.